2024
DOI: 10.1039/d4ra00423j
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biological studies and computational prediction-based analyses of pyrazolo[1,5-a]pyrimidine derivatives

Abdulrahman A. Almehizia,
Wael M. Aboulthana,
Ahmed M. Naglah
et al.

Abstract: Recently, new pharmaceutical discoveries have become very important for addressing diverse health problems and protecting humanity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 106 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Almehizia and his colleagues' research indicated that pyrazolo [1, 5-a]pyrimidine derivatives possess various biological activities against cancer, diabetes, Alzheimer's disease, and inflammation. Therefore, they were suggested as multi-target agents [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Almehizia and his colleagues' research indicated that pyrazolo [1, 5-a]pyrimidine derivatives possess various biological activities against cancer, diabetes, Alzheimer's disease, and inflammation. Therefore, they were suggested as multi-target agents [8].…”
Section: Introductionmentioning
confidence: 99%